Controlled decompression attenuates brain damage in a rat model of epidural extreme intracranial hypertension: Partially via inhibiting necroptosis and inflammatory response. (February 2022) - Qian, Xiao; Zhang, Chonghui; Zhou, Zhaopeng; Cao, Xinyi; Zhang, Chunlei; Chen, Tao; Wang, Yuhai
Abstract: Intracranial hypertension (IH) remains a common symptom of neurological diseases, and requires stepwise treatments to release intracranial pressure (ICP). In the present study, we built a rat model of epidural extreme intracranial hypertension (EEIH) and verified the effectiveness of a surgery method called controlled decompression on attenuating brain injury induced by EEIH. For the model part, we determined the level of EEIH of rats via recording ICP and cerebral perfusion pressure (CPP) and the variation tendency of survival rates, mean blood artery pressure and mean velocity (Vm) of left middle cerebral artery (LMCA) as ICP ascending. SD rats were assigned into 4 groups: Sham group, Controlled decompression group (Con group), Rapid decompression group (Rap group) and Rapid decompression + Necrostatin-1 (Nec-1) group (Rap+Nec-1 group). The results suggested that controlled decompression lowered cerebral water content, improved neurological function, and attenuated EEIH-induced inflammation response and ROS generation to a greater extent than rapid decompression. Meanwhile, controlled decompression functioned to preserve more Nissl bodies, indicating alleviated neuron injury after EEIH. Additionally, the permeability of blood brain barrier (BBB) was also safeguarded in the Con group. Western blotting (WB) and Real-time Polymerase Chain Reaction (rt-PCR) assays consistently determined lower protein and mRNA levels of necroptosis-related molecules receptor interacting protein kinase 1 (RIPK1), interacting protein kinase 3 (RIPK3) and mixed lineage kinase domain-like protein (MLKL) (WB only) in the Con and Rap+Nec-1 group. Double immunofluorescent staining found weaker fluorescence intensity of RIPK3 in the compressed cortex of the Con and Rap+Nec-1 group. Highlights: This is an animal experiment concerning a novel surgery technique, controlled decompression, for treating epidural extreme intracranial hypertension (EEIH). We recorded the vital signs of rats under different ranks of intracranial pressure and further successfully determined the level of EEIH. Based on that, an EEIH model of rats was built to corroborated the effectiveness of controlled decompression in reducing brain injury. Controlled decompression could effectively improve neurological scoring and attenuate brain edema content, neuro-apoptosis, inflammation response, neuro-death and BBB damage caused by EEIH in rats. The role of controlled decompression may attribute to the inhibition of necroptosis process activated by TNF-1.